Analysis of the Judge's Decision Regarding Polygamy Permits from the Perspective of Maqāṣhid Al-Syarī'ah in the Toli-Toli Religious Court - mohfalatehan; Muh. Akbar; Hilal Malarangan; Muh. Amin P (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2024)
This article discusses the statutory provisions that regulate the requirements for polygamy permits intended to create public order, provide legal protection and guarantees for rights and obligations arising from legal relationships in terms of how important it is to obtain court permission for polygamy, formally the urgency of granting polygamy permits must be realized. Legal certainty, order, protection, and legal guarantees for marriage itself. Polygamy permit provisions are implemented to protect the interests, rights, and obligations arising from a marriage. The method used in this research is qualitative, with data collection techniques carried out through direct observation, in-depth interviews, and analysis of written documents. The results of this research show that the granting of the request for a polygamy permit was also due to the applicant's economic capabilities and the willingness and encouragement of the first wife for her husband to carry out polygamy. Thus, there would be no dharar that would be affected by the first wife, so granting the request for a polygamy permit is believed to be able to achieve benefits for all parties involved in the marriage so that the purpose of marriage, as in the provisions of Article 3 of the Compilation of Islamic Law is to create a household life in which Sakinah, mawaddah, and warahmah can be realized. So, it can be concluded that the decision of the Tolitoli Religious Court case number 318/Pdt.G/2022/PA.Tli is still in line with the maqashid as-shari'ah according to as-syatibi, namely protecting religion, soul, mind, property, and lineage.